(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The study’s objective is to develop apixaban-loaded solid lipid nanoparticles (SLN), which provide an increased permeability and sustained release compared to tablet formulations. The design of experiments (DoE) is employed in the development and optimization of SLNs. SLNs were manufactured using hot homogenization followed by an ultra-sonication method. Initially, screening of lipids and surfactants (both qualitative and quantitative variability) was done by mixture design. Furthermore, the formulation was optimised using central composite design considering the concentration of both lipid and surfactant as factors and particle size, polydispersity index (PDI), encapsulation efficiency (EE), zeta potential, and percent drug release as responses. Statistical evaluation was performed to get the optimised formulation composition, i.e., glyceryl monooleate (GMO) -6.7% and polysorbate 80-3%. The surface morphology has shown that the SLNs were spherical with a particle size of 239.33 ± 10 nm, PDI of 0.135 ± 0.015, EE of 78.00 ± 2% and zeta potential of -26.4 ± 0.75 mV. %drug release from the optimised formulation was extended to 24 hours. In-vitro release showed the initial burst release was followed by a persistent release lasting up to 24 hours. The ex-vivo permeation studies revealed that the permeability of the optimised SLN formulation is increased by 1.9 and 1.3 times compared to pure drug and tablet formulations. The stability results showed that the optimised formulations were stable for up to 6 months at 2–8℃ and 25 ± 5℃/60 ± 5% RH. These findings suggest that the apixaban SLNs could be used as a delivery system with higher bioavailability and longer drug release.